2014
DOI: 10.1038/bmt.2014.166
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and outcomes in patients⩾60 years of age after allogeneic hematopoietic cell transplantation

Abstract: Hematopoietic cell transplantation (HCT) has become an established standard of care for many older patients with hematologic malignancies. The effect of transplantation on the quality of life (QOL) of older patients, however, has not been well studied. We thus analyzed QOL in patients ⩾ 60 undergoing an allogeneic HCT compared with patients o 60 years. Prospective psychometric instruments were administered to 351 patients who underwent HCT from 2003 to 2010. Psychometric data were assessed longitudinally by va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 36 publications
(39 reference statements)
2
13
0
Order By: Relevance
“…Many factors predict survival outcomes after allogeneic HCT, including patient age, comorbidities, donor source, performance status, diagnoses, disease status, and carepartner support. Although several studies have investigated and described QOL after transplantation, including the trajectory of QOL risk factors for QOL impairments and interventions to improve QOL, [13][14][15][16][17][18][19][20] the association of pre-transplantation QOL with recovery and survival after allogeneic HCT has not been well described. We hypothesized that QOL measures before HCT may add to the prognostic information provided by known clinical factors among allogeneic HCT recipients.…”
Section: Introductionmentioning
confidence: 99%
“…Many factors predict survival outcomes after allogeneic HCT, including patient age, comorbidities, donor source, performance status, diagnoses, disease status, and carepartner support. Although several studies have investigated and described QOL after transplantation, including the trajectory of QOL risk factors for QOL impairments and interventions to improve QOL, [13][14][15][16][17][18][19][20] the association of pre-transplantation QOL with recovery and survival after allogeneic HCT has not been well described. We hypothesized that QOL measures before HCT may add to the prognostic information provided by known clinical factors among allogeneic HCT recipients.…”
Section: Introductionmentioning
confidence: 99%
“…31 A review article by Pidala et al 32 found that older age, advanced disease at transplant, chronic GvHD, lower functional status and less social support were predictors of poorer QOL post-HCT. In contrast, Hamilton et al 33 found that older survivors achieved comparable QOL to younger survivors. Figure 1.…”
Section: Functional Considerationsmentioning
confidence: 93%
“…One study suggests that older patients experience worse physical well-being but better social well-being compared to their younger counterparts [ 70 ]. Other studies are mixed suggesting that older patients may achieve better, comparable, or worse QoL than younger patients [ 71 , 72 , 73 ].…”
Section: Graft-versus-host Disease In the Older Transplant Patientmentioning
confidence: 99%